Training and technology transfer course performance objectives manual (TT1-01). (Manila, Philippines, 1990)
In 1986, the International Rice Research institute designed the Training and Technology Transfer Course (T3C). The T3C offers instruction on the latest advances in education and information technology. For effective training, IRRI applies innovative training methods and modern educational technology. One of these is the use of performance objectives. These objectives define exactly the tasks that a learner should be able to do after instruction. They simplify instruction and make measurement of learning achievements easy. A manual of performance objectives can be a useful guide for trainers in developing a curriculum that meets specific needs. This manual compiles performance objectives for the T3C. It aims primarily to facilitate the trainee’s learning process.
Keywords: Agricultural extension workers,Technology transfer; Training of,Developing countries.,Study and teaching,Developing countries